The Associations Between Clerkship Objective Structured Clinical Examination (OSCE) Grades and Subsequent Performance. Issue 3 (3rd July 2017) - Dong, Ting; Zahn, Christopher; Saguil, Aaron; Swygert, Kimberly A.; Yoon, Michelle; Servey, Jessica; Durning, Steven
ABSTRACT: Construct: We investigated the extent of the associations between medical students' clinical competency measured by performance in Objective Structured Clinical Examinations (OSCE) during Obstetrics/Gynecology and Family Medicine clerkships and later performance in both undergraduate and graduate medical education. Background: There is a relative dearth of studies on the correlations between undergraduate OSCE scores and future exam performance within either undergraduate or graduate medical education and almost none on linking these simulated encounters to eventual patient care. Of the research studies that do correlate clerkship OSCE scores with future performance, these often have a small sample size and/or include only 1 clerkship. Approach: Students in USU graduating classes of 2007 through 2011 participated in the study. We investigated correlations between clerkship OSCE grades with United States Medical Licensing Examination Step 2 Clinical Knowledge, Clinical Skills, and Step 3 Exams scores as well as Postgraduate Year 1 program director's evaluation scores on Medical Expertise and Professionalism. We also conducted contingency table analysis to examine the associations between poor performance on clerkship OSCEs with failing Step 3 and receiving poor program director ratings. Results: The correlation coefficients were weak between the clerkship OSCE grades and the outcomes. The strongest correlations existed between the clerkship OSCE grades and the Step 2 CS Integrated Clinical Encounter component score, Step 2 Clinical Skills, and Step 3 scores. Contingency table associations between poor performances on both clerkships OSCEs and poor Postgraduate Year 1 Program Director ratings were significant. Conclusions: The results of this study provide additional but limited validity evidence for the use of OSCEs during clinical clerkships given their associations with subsequent performance measures.